The Possible Involvement of HLA Class III Haplotype (RAGE, HSP70 and TNF Genes) in Alzheimer's Disease - Boiocchi, Chiara; Maggioli, Elisa; Cristina Monti, Maria; Zorzetto, Michele; Sinforiani, Elena; Cereda, Cristina; Ricevuti, Giovanni; Cuccia, Mariaclara (Current Alzheimer Research, 2015)
In the central nervous system Hsp70s seems to have a protective role in repair and removal of cellular proteins damaged by stress conditions. A protective role of Hsp70 was also shown in Alzheimer Disease. The HSP70-1 +190 G/C polymorphism is located in the gene 5’UTR region and it is implicated in alteration of the transcription binding factor; HSP70-2 +1267 A/G causes a silent mutation in the coding region and it seems to influence the mechanism of mRNA translation; HSP70-hom +2437 A/G causes a substitution Met → The (M493T) in the coding region and it seems to influence the bond with the substrate and therefore on the chaperone activity of hsp70. The aim of our study will be to investigate Alzheimer susceptibility to Hsp70 polymorphisms, taking into account our previous findings on HLA class III region, and to hypothesize a role of HLA class III haplotype configuration based on the variants of three genes: RAGE, HSP70 and TNF. We studied these polymorphisms with PCR-RFLP and PCR-TSP. We investigated 173 AD patients and 211 control subjects. Our results have shown a statistically significant decrease of the C allele frequency of the HSP70-1 +190 G/C polymorphism in AD patients vs controls (P value = 0,018), as well as the G allele of HSP70-2 +1267 G/A (p value = 0,02). We focalized our attention on haplotype reconstruction. We have observed a significant statistically decrease of GGT haplotype frequency (empirical p-value=0.0133 ); GAT haplotype was statistically significant increase in AD patients compared with control (empirical p-value=0.007). The total HLA class III haplotype are reconstructed. The causative haplotypes are the following ones: TTGATGGG ( p value =0,005; empirical p =0,0042); TTGATAGG (p value =0,45; empirical p =0,034). Patients with these haplotypes may show an earlier onset of the disease than patients with TTGGTGGG (p value=0,0138; empirical p =0,0102); TTCGTGGG (p value=0,021; empirical p =0,017); TTCGTGGA (p value =0,058; empirical p =0,043) haplotypes. The overall variation of the haplotypes formed by the RAGE and TNF and HSP70 variants influenced the presence of the AD phenotype (omnibus association LR test p-value 0.00185), HSP701 and HSP702 showed independent effect on AD risk after adjusting for the effect of the entire haplotype (conditional LR test p-value=0.0114 and p-value=0.0044 respectively). These data confirm the involvement of HLA class III in AD.
Keywords: neurodegeneration